2021
DOI: 10.1074/jbc.ra120.013997
|View full text |Cite
|
Sign up to set email alerts
|

KCa3.1-dependent uptake of the cytotoxic DNA-binding dye Hoechst 33258 into cancerous but not healthy cervical cells

Abstract: The poor and nonselective penetration of current chemotherapeutics across the plasma membranes of cancer cells, which is necessary for the targeted disruption of the intracellular machinery, remains a major pharmaceutical challenge. In several cell types, including mast cells and macrophages, exposure to extracellular ATP is known to stimulate passive entry of large and otherwise membrane impermeable cationic dyes, which is usually attributed to conduction through ionotropic P2X receptors. Here, we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…To improve chemotherapy outcomes, a widely used alternative is to sensitize cancer cells to cytotoxic drugs by increasing their permeability, considering that several anticancer drugs, such as cisplatin and doxorubicin, have low membrane permeability. Bukhari et al found that the activation of the intermediate conductance Ca 2+ -activated K + channels (K Ca 3.1), which is upregulated in CCa cells, induces H33258 uptake, a cytotoxic DNA-binding cationic dye [ 23 ].…”
Section: Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve chemotherapy outcomes, a widely used alternative is to sensitize cancer cells to cytotoxic drugs by increasing their permeability, considering that several anticancer drugs, such as cisplatin and doxorubicin, have low membrane permeability. Bukhari et al found that the activation of the intermediate conductance Ca 2+ -activated K + channels (K Ca 3.1), which is upregulated in CCa cells, induces H33258 uptake, a cytotoxic DNA-binding cationic dye [ 23 ].…”
Section: Potassium Channelsmentioning
confidence: 99%
“… mRNA and protein overexpression in cervical cancer tissues. [ 23 , 32 , 33 ] Ovarian cancer K 2p 2.1 K 2p 10.1 Curcumin increases late apoptosis and decrease proliferation in SK-OV-3 and OVCAR-3 cells. Expression is increased in cancer samples compared to normal ovarian samples.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…TRPV3 (transient receptor potential cation channel subfamily V member 3 or transient receptor potential vanilloid 3) is mainly expressed in keratinocytes and is activated by repetitive thermal stimuli [262]. The overexpression of TRPV3 in NSCLC is able to influence cell proliferation, channel blocking decreases the colony-forming capacity of cell lines, and the cell cycle is arrested in the G 1 /S phase (Table 2) [140]. The transient receptor potential cation channel subfamily V member 4 (or transient receptor potential vanilloid 4, TRPV4) is expressed in many tissues, is involved in the perception of various physical and chemical stimuli, and its expression has been associated with several neurodegenerative disorders [266].…”
Section: Transient Receptor Potential Cation Channelsmentioning
confidence: 99%